Analisis Yuridis Terhadap Penanganan Kapal Asing Yang Melintas Tanpa Izin Di Wilayah Perairan Indonesia Berdasarkan Hukum Laut Internasional - Hani zulfa shofyanti; Nadila Melanie putri; Siska Valentina Pardosi (GLOBAL SCIENTS PUBLISHER, 2026)
This analysis focuses on a legal review of the handling of foreign vessels that pass through Indonesian waters without permission, with reference to international maritime law provisions. The urgency of this study is based on Indonesia’s geographical position as an archipelagic country with vast seas and vital global shipping lanes. The activities of foreign vessels that do not comply with regulations risk disrupting sovereignty, maritime security, and the sustainability of marine resources. In terms of methodology, this study uses a normative legal approach, which combines analysis of legislation and legal concepts. As an archipelagic country, Indonesia has the legal legitimacy to conduct surveillance, control, and law enforcement actions against foreign vessels that do not comply with regulations in its waters. Existing national regulations further strengthen Indonesia’s jurisdiction in protecting its sovereignty and maritime interests. Therefore, it is necessary to improve the maritime surveillance system and synergy between law enforcement agencies to ensure the protection of Indonesia’s territorial waters is optimal in accordance with international legal standards.